2013
DOI: 10.1002/app.40260
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cationic magnetite nanoparticles for intracellular protein delivery

Abstract: Intracellular protein delivery shows great promise in the treatment of various diseases. However, therapeutic applications of this method are limited by its low delivery efficiency and poor targeting ability. As one of most important drug delivery cargoes, Fe3O4 nanoparticles (nFe3O4) have attracted much attention for both therapeutic and diagnostic applications, especially for targeting drug delivery. To use nFe3O4 for protein delivery, a simple but effective modification of nFe3O4 is critical to attach prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Cell apoptosis was observed only when a magnetic field was used, demonstrating cytosolic delivery of caspase 3. Other magnetic protein carriers were produced by classical methods, either by covalent or noncovalent linking of polymers onto the surface of SPIO . These carriers transduced BSA and GFP inside the cytosol in a magnetic field‐dependent manner.…”
Section: Transduction With Exotic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell apoptosis was observed only when a magnetic field was used, demonstrating cytosolic delivery of caspase 3. Other magnetic protein carriers were produced by classical methods, either by covalent or noncovalent linking of polymers onto the surface of SPIO . These carriers transduced BSA and GFP inside the cytosol in a magnetic field‐dependent manner.…”
Section: Transduction With Exotic Nanoparticlesmentioning
confidence: 99%
“…Other magnetic protein carriers were produced by classical methods, either by covalent or noncovalent linking of polymers onto the surface of SPIO. [165] These carriers transduced BSA and GFP inside the cytosol in a magnetic field-dependent manner. Nevertheless, the use of SPIO nanoparticles for large molecule transduction requires improved delivery efficiency, including strategies to reduce/ avoid long term SPIO nanoparticles accumulation in animal, favoring biological elimination.…”
Section: Superparamagnetic Iron Oxide (Spio) Nanoparticles and Magnet...mentioning
confidence: 99%
“…The experimental results revealed that compressive strength of polyurethane foam decreased significantly after degradation, and the ester/hydroxyl band ratio was a good indicator to assess the degradation degree. Wang et al . investigated the thermal decomposition kinetics of RPUF in oxidative atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…More elaborate 1-D models have also been developed for flaming ignition [28]. A related problem is the spot fire ignition of polymer foams found in industrial and urban environments has also been studied [29][30][31].…”
Section: Introductionmentioning
confidence: 99%